Penerapan Metode Fuzzy Logic-PID Sebagai Kontrol Gerak Robot Berkaki Enam (Hexapod) - Subur, Joko; Suryadhi, Suryadhi; Arohman, Eki (Proceedings Series on Physical & Formal Sciences, 2023)
Robotics technology is currently developing rapidly and has become one of the sophistications that are relied upon by every country, one of which is Indonesia. One of the activities for the development of robotics technology in Indonesia is the Indonesian Robot Contest (KRI). KRI was held as an event for students' creativity in designing robots. One of the divisions contested at KRI is the Indonesian Search and Rescue Robot Contest (KRSRI) division. In the KRSRI division, it is required to make a legged robot that can navigate the motion of walking in the competition area and pass obstacles on the track. Of course, a navigation motion control system is needed that can regulate the movement of the legged robot's steps properly, so that the robot can pass the path in the arena. In this study, the answer to this problem is the application of legged robot navigation motion control using the Fuzzy Logic-PID method. The Fuzzy Logic-PID method is a combination of two methods between the Fuzzy Logic Controller method and the Proportional Integral Derivative (PID) control method. The Fuzzy method’s role is to produce constant values ??P, I, and D based on the error value and the incoming error delta. Furthermore, the resulting constant value is used in the calculation of the PID control. From the experimental data, the Fuzzy method has been able to produce a PID constant value and the PID method can also be applied to regulate the robot's motion steps. The test results on trials using obstacles and without obstacles were successful, except for uphill obstacles with a success percentage of 60% successfully passing incline obstacles and 40% failing to pass uphill obstacles.